Women's Empowerment Through PKK Dawis 2 Group RT 37 RW 009 Surodinawan Village, Prajurit Kulon District, Mojokerto City in Orderly Administration and Financial Bookkeeping - Eny Nuraeni; Sugeng Eko Yuli Waluyo; Buyung Cahya Perdana; Dwi Sembe Sigita (PT. Gudang Pustaka Cendekia, 2025)
Women's empowerment at the grassroots level is often constrained by weak administrative practices and the absence of transparent financial management systems. This research aims to analyze how orderly administration and financial bookkeeping can strengthen women’s empowerment within the PKK Dawis 2 group in Surodinawan Village, Mojokerto City. Using a descriptive qualitative method with a case study approach, data were obtained through interviews, observations, and document analysis. The implementation of structured administrative procedures, including agenda preparation, attendance recording, and systematic documentation, resulted in increased participation, clearer decision-making processes, and stronger organizational coordination. Likewise, the adoption of basic financial bookkeeping enabled members to record income and expenditures accurately, prepare monthly financial reports, and improve accountability in managing community funds. The findings show that training and guided practice helped members build confidence, develop financial literacy, and contribute more actively to organizational activities. Overall, the study concludes that strengthening administrative discipline and transparent bookkeeping significantly enhances women’s agency and organizational resilience, offering a practical model for similar community groups.